2023
DOI: 10.1002/pei3.10100
|View full text |Cite
|
Sign up to set email alerts
|

Volatile responses of dwarf birch to mimicked insect herbivory and experimental warming at two elevations in Greenlandic tundra

Abstract: Plants release a complex blend of volatile organic compounds (VOCs) in response to stressors. VOC emissions vary between contrasting environments and increase with insect herbivory and rising temperatures. However, the joint effects of herbivory and warming on plant VOC emissions are understudied, particularly in high latitudes, which are warming fast and facing increasing herbivore pressure. We assessed the individual and combined effects of chemically mimicked insect herbivory, warming, and elevation on dwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Previous studies on dwarf birch showed no effects of warming on the VOC blend (Rieksta et al., 2021, 2023a) when analyzed using random forests, a simple machine learning technique. However, using ASCA, which allows for the investigation of interaction effects on VOC blends, we were able to detect differences in the VOC blends.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Previous studies on dwarf birch showed no effects of warming on the VOC blend (Rieksta et al., 2021, 2023a) when analyzed using random forests, a simple machine learning technique. However, using ASCA, which allows for the investigation of interaction effects on VOC blends, we were able to detect differences in the VOC blends.…”
Section: Discussionmentioning
confidence: 92%
“…Climate manipulation experiments at high latitudes generally show positive warming effects on VOC emissions (Faubert et al., 2010; Ghirardo et al., 2020; Kramshøj et al., 2016; Lindwall et al., 2016; Rinnan et al., 2020; Valolahti et al., 2015). However, weak or complex effects of warming on VOC emissions have also been reported (Rieksta et al., 2021, 2023a; Rinnan et al., 2011; Schollert et al., 2015). In our data, most VOCs were unaffected by warming, but GLV emission rates doubled in response to warming and this response remained even when emissions were standardized by temperature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations